BASIC EDUCATION AND ECONOMICS REFORM OF SUBSIDY REMOVAL IN NIGERIA: IMPLICATIONS FOR EDUCATIONAL ADMINISTRATION AND PLANNING - Temitope Zuifah Mustapha (PT. Antis International Publisher, 2025)
Objective: This paper examines Basic education and economics reform of subsidy removal in Nigeria with focus on implication for educational administration and planning. Method: The study uses quantitative methods to analyze data from various sources including government reports, academic articles, and surveys. Results: The paper revealed that the gains of subsidy removal in Nigeria on education include; increased government revenue for education investment, enhanced funding for educational infrastructure, strengthening teacher welfare and capacity development, promotion of equity through reinvestment in social programs and encouragement of public-private partnerships in education. The paper also disclosed that increased cost of living for families, reduced access and affordability of education, strain on educational administrators and planners, potential decline in teacher welfare and morale and widening inequality in education access. Novelty: The study recommends that government should ensure that a significant portion of the savings from subsidy removal is directly allocated to basic education. Policymakers and educational planners must adopt data-driven approaches to ensure that resources are distributed equitably across states and local governments. To cushion the effect of inflation on teachers, government should adjust salaries and allowances in line with current economic realities. Conditional cash transfers, scholarships, and provision of free uniforms and textbooks should be expanded to ensure that children from low-income households are not excluded from school due to financial hardship.